Revealing the structures of megadalton-scale DNA complexes with nucleotide resolution - Massimo Kube (Nature Portfolio, 2020)
Precision design of DNA origami needs precision validation. Here, the authors developed cryo-EM methods for obtaining high resolution structural data and for constructing pseudo-atomic models in a semi-automated fashion, allowing for iterative nanodevice inspection and refinement.